MENGEMBANGKAN KREATIVITAS PADA ANAK MELALUI KEGIATAN FINGER PAINTING DI DESA MEDALKRISNA - Nurahma, Helsya; Arrahim, Arrahim; Ramadhan, Fakhran (An-Nizam, 2024)
Creativity is an important demand of education at present. Individuals with creativity will always be needed by the environment because they are able to meet the constantly changing needs of the environment. However, not all children have high creativity; one of the reasons for the low creativity in children is because they are still shy and lack confidence in expressing their imagination. Therefore, this program aims to develop children's creativity through finger painting activities as they stimulate creativity in children. The method used in its implementation is by providing finger painting training. The training includes mixing colors, forming patterns, making strokes, and forming images, trying to paint pictures using Finger Painting media according to their creativity. They are given the opportunity to try finger painting according to their respective creativity. Based on the results of the activity implementation, it can be seen that finger painting activities can increase children's creativity because children show active participation in finger painting activities, they are able to work independently and complete their work, and they are able to express themselves and their ideas creatively through finger painting. This activity provides many benefits, insights, and knowledge to children, especially in helping to stimulate children's creativity using finger painting to build self-confidence.